2022
DOI: 10.1186/s12913-022-08635-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of various appointment systems among patients visiting academic outpatient centers in Kerman and the evaluation of patients’ perspective and satisfaction

Abstract: Background To optimize appointment systems, it is necessary to assess their users’ perspectives. This study aims to determine the use of various appointment systems among patients in academic outpatient centers and to investigate their perspectives and satisfaction. Methods This survey study was conducted on 332 patients or those accompanying patients in academic outpatient centers. A five-part questionnaire consisting of (1) demographic informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In fact, most studies reported that appointment systems signifi­cantly reduce the time of arranging appointments and save the participants’ time [ 12 ]. This result is consistent with the results of studies [ 10 , 15 , 21 - 23 ], which have shown that appointment systems can effectively reduce waiting time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, most studies reported that appointment systems signifi­cantly reduce the time of arranging appointments and save the participants’ time [ 12 ]. This result is consistent with the results of studies [ 10 , 15 , 21 - 23 ], which have shown that appointment systems can effectively reduce waiting time.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies assessing web-based systems documented their efficiency, and most patients would use the service again [7][8][9][10][11][12][13][14][15][16][17]. To date, there are few studies about the efficacy of web-based appointment systems in Saudi Arabia [18].…”
Section: Introductionmentioning
confidence: 99%
“…Literature shows that integration of patient centered scheduling systems through web-based or interactive voice response systems could lead to better accessibility and availability of care. 20,21 While there are technical solutions to improving appointment availability, lack of providers accepting the TRICARE benefit is a continuing challenge. 22 In addition to increased choice and flexibility, participants wanted high-quality care.…”
Section: Discussionmentioning
confidence: 99%